Teacher support as predictors of Chinese EFL learners’ classroom flow: the mediating role of academic self-efficacy - Gong, Wenting; Xu, Chuang (Frontiers in Psychology, 2024)
Informed by social support theory and control-value theory, this study investigates the predictive role of teacher support on classroom flow among English as a Foreign Language (EFL) learners and the mediating effect of academic self-efficacy. A survey was conducted among 557 Chinese university EFL learners to gather relevant data. Descriptive statistics indicate that the participants exhibited a moderate level of classroom flow and exhibited significant variations based on gender and grade. Analysis using structural equation modeling revealed that teacher support has a noteworthy, positive predictive impact on EFL learners’ classroom flow. Furthermore, academic self-efficacy serves as a partial mediator between teacher support and classroom flow, with instrumental and emotional teacher support showing the strongest indirect effects. Notably, various dimensions of teacher support, aligning with students’ psychological needs as outlined by self-determination theory, have unique predictive effects on both classroom flow and academic self-efficacy. Appraisal and informational teacher support have the greatest predictive influence on classroom flow among the teacher support considered. The findings enhance understanding of the dynamics between teacher support, academic self-efficacy, and classroom flow, offering practical implications for creating autonomy-supportive educational environments that can elevate EFL learners’ engagement and academic achievements.